Aberrant HRAS transcript processing underlies a distinctive phenotype within the RASopathy clinical spectrum. Issue 7 (3rd May 2017) - Pantaleoni, Francesca; Lev, Dorit; Cirstea, Ion C.; Motta, Marialetizia; Lepri, Francesca Romana; Bottero, Lisabianca; Cecchetti, Serena; Linger, Ilan; Paolacci, Stefano; Flex, Elisabetta; Novelli, Antonio; Carè, Alessandra; et al.
Abstract : Aberrant HRAS transcript processing promoting constitutive retention of exon IDX leads to altered HRAS function resulting in a mild hyperactive protein, which is constitutively targeted to the plasma membrane. This new mechanism underlies a distinctive and previously unappreciated phenotype within the RASopathy clinical spectrum. Abstract: RASopathies are a group of rare, clinically related conditions affecting development and growth, and are caused by germline mutations in genes encoding signal transducers and modulators with a role in the RAS signaling network. These disorders share facial dysmorphia, short stature, variable cognitive deficits, skeletal and cardiac defects, and a variable predisposition to malignancies. Here, we report on a de novo 10‐nucleotide‐long deletion in HRAS (c.481_490delGGGACCCTCT, NM_176795.4; p.Leu163ProfsTer52, NP_789765.1) affecting transcript processing as a novel event underlying a RASopathy characterized by developmental delay, intellectual disability and autistic features, distinctive coarse facies, reduced growth, and ectodermal anomalies. Molecular and biochemical studies demonstrated that the deletion promotes constitutive retention of exon IDX, which is generally skipped during HRAS transcript processing, and results in a stable and mildly hyperactive GDP/GTP‐bound protein that is constitutively targeted to the plasma membrane. Our findings document a new mechanism leading to altered HRAS function that underlies a previously unappreciated phenotype within the RASopathy spectrum.